Effect of Acupuncture Therapy Combination of Curcuma Xanthorrhiza Extract on Changes in Scale of Stomach Pain in Students of Campus 1 Polytechnic of the Ministry of Health Surakarta - Meutia Wahdini Nurhaiqa; Eka Deviany Widyawaty; Sumanto; Nurmila Mutiah (Indonesian Journal of Acupuncture, 2026)
Stomach pain or dyspepsia is a digestive disorder characterized by epigastric pain, a feeling of fullness, nausea, vomiting, and frequent belching. Although often considered mild, this condition poses a risk of serious complications such as peptic ulcers, perforation, and even stomach cancer, which can significantly impact the quality of life. This study aims to determine the effect of acupuncture therapy combined with turmeric extract on changes in the stomach pain scale among students at Campus 1 Poltekkes Kemenkes Surakarta. The study employed a "Quasi-Experimental" design with a two-group pretest and posttest design. A total of 34 subjects were selected using purposive sampling and divided into two groups of 17 individuals each. The results of the Wilcoxon test showed a significance level of p < 0.05, indicating a significant effect on changes in the stomach pain scale within each group. Meanwhile, the Mann-Whitney test results between the two groups yielded a significance value of p = 0.004. Since the p-value < 0.05, there is a meaningful difference between the two groups, which means that Ha is accepted and H0 is rejected. This indicates that acupuncture therapy combined with turmeric extract has a significant effect on changes in the stomach pain scale among students at Campus 1 of the Ministry of Health Polytechnic of Surakarta.